Pervasive computing in sports - Baca, A. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
The Integration of modern sensor-, information- and communication technologies provides promising means for developing systems to acquire, process and wirelessly transmit data during sportive activities. Four fields of application are pointed out and illustrated by recent examples. Coaching is considered first, introducing ihe concept of remote coaching. Sensors acquire athletes' performance data; the digitized signals are transmitted to a mobile client and from this sent to an internet server. Coaches and sports scientists may thus give fast feedback not only at the training site but also from remote locations. The potential of markerless and wireless tracking methods is outlined then, giving an example from marathon running, where athletes are informed on their position and average velocity as well as the position of their running partners during the race. Third,systems for quantifying and/or qualifying sports and physical activity are discussed. They include systems for collecting distances run and for estimating running intensities, systems for supervising rules and regulations and systems for supporting judges. An example from taekwondo is given, where force sensors in body protectors assist judges in scoring correctly. Applications in leisure and entertainment activities are finally considered. Concluding, some future expectations are given.